The presidential re-election in Latin America: abreakthrough into warlordism and a setback fordemocracy - Cárdenas-Hernández, Carlos Alfonso (Universidad Pedagógica y Tecnológica de Colombia, 2014)
Warlordism is the political regime that characterizes the political culture in Latin American, and the re-election is a tool used by the supporters of this system to stay in power at the expense of republican democracy. Hence, to ensure the exercise of this democracy, the exercise of presidential power must be limited to a reasonable period, without re-election, to strengthen political parties, that invigorates democracy.